1979
DOI: 10.1136/jnnp.42.11.1031
|View full text |Cite
|
Sign up to set email alerts
|

Memory in functional psychosis.

Abstract: S U M MARY Acute schizophrenic, chronic schizophrenic, and depressive patients (20 of each) were compared with normal subjects and six groups of patients with organic brain disease. They were given tests of verbal learning (left hemisphere type function) and pattern recognition memory (right hemisphere type function). All functional psychotics showed impaired memory. Acute schizophrenics were, however, only impaired on the verbal task, suggesting left hemisphere dysfunction, while chronic schizophrenics and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…The question of whether depression can produce intellectual impairment which mimics that due to brain disease is an interesting one. Such studies as have demonstrated an unequivocal relationship between depression and intellectual impairment, with intellectual improvement following treatment of the mood disorder, have tended to involve studies of severely depressed psychiatric inpatients (Stromgren, 1977, Cutting 1979. Reports concerning less sever1 y depressed patients have produced inconsistent findings on the influence of depression on tests of memory, intellectual speed, problem solving strategies and certain verbal performance tasks (Kendrick & Post 1967, Miller 1975, Glass et al, 1981, Cohen et al, 1982.…”
Section: The Effects Of Mood Disorder On Longterm Outcome In the Stromentioning
confidence: 99%
“…The question of whether depression can produce intellectual impairment which mimics that due to brain disease is an interesting one. Such studies as have demonstrated an unequivocal relationship between depression and intellectual impairment, with intellectual improvement following treatment of the mood disorder, have tended to involve studies of severely depressed psychiatric inpatients (Stromgren, 1977, Cutting 1979. Reports concerning less sever1 y depressed patients have produced inconsistent findings on the influence of depression on tests of memory, intellectual speed, problem solving strategies and certain verbal performance tasks (Kendrick & Post 1967, Miller 1975, Glass et al, 1981, Cohen et al, 1982.…”
Section: The Effects Of Mood Disorder On Longterm Outcome In the Stromentioning
confidence: 99%
“…Patients with schizophrenia frequently show problems with episodic memory, including impaired acquisition and poor recall of information and, to a lesser extent, impaired recognition (e.g., Beatty et al, 1993;Calev et al, 1983;Clare et al, 1993;Cutting, 1979;Gold et al, 1992a,b;Goldberg et al, 1989;Kolb & Whishaw, 1983;Landro, 1994;Mc-Kenna et al, 1990;Paulsen et al, 1995;Saykin et al, 1991;Tamlyn et al, 1992). However, the clinical heterogeneity of schizophrenia is likely to influence the extent to which deficits in memory represent discrete cognitive impair-ments.…”
Section: Introductionmentioning
confidence: 99%
“…These deficits were recognized in the original clinical accounts of the disorder by Kraepelin (1 9 19) and Bleuler (1 950). Conventional wisdom concerning schizophrenia suggests cognitive deficits, particularly in memory, arise because of attention deficits shown by schizophrenic subjects (Cutting, 1979;Grebb and Cancro, 1989), but converging evidence now indicates a more complex picture. The association of cognitive deficits with neuroanatomical abnormalities in the brains of schizophrenic subjects, especially in the medial temporal sites implicated in memory function (Andreasen et al, 1990(Andreasen et al, , 1982Johnstone et a]., 1976;Pearlson et al, 1989), supports a neurodevelopmental hypothesis for the aetiology of schizo-phrenia beyond attention disorders.…”
Section: Discussionmentioning
confidence: 99%